Sistema de autoavaliação de aplicado a programas de mestrado em rede - Soares, Gustavo Fernandes (2018)
The aim of this study was to develop a self-assessment system for master’s degree programs in network. To support the construction of this system, this study developed a research about the self-evaluation experiences of stricto sensu graduate programs in Brazil and Portugal, as well as an evaluation of criteria used by CAPES and the characteristics of master’s programs. It were identified and classified seventy-four indicators into seven dimensions that allow evaluating the programs regarding the participants' profile; actuation and integration; pedagogical planning; administrative planning; infrastructure; sustainability and technical and scientific production. The system developed was applied and validated in the PROFIAP Master's Program, and it demonstrated functionality and ability to produce information. The results of the self-assessment were analyzed using descriptive analysis and Exploratory Factor Analysis. It was elaborated an implementation plan that guides the use of the proposed system. The proposed indicators proved to be effective for a system of self-evaluation of master's degree programs in network. The dimensions and indicators of evaluation found in this research are certainly not exhaustive and the great diversity between the master’s degree programs makes this study open to adaptations.